DETERMINATION OF Z0 RESONANCE PARAMETERS AND COUPLINGS FROM ITS HADRONIC AND LEPTONIC DECAYS - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; et al. (1991)
From measurements of the cross sections for e+e-→ hadrons and the cross sections and forward-backward charge-asymmetries for ee-→e+e-, μ+μ- and π+π- at several centre-of-mass energies around the Z0 pole with the DELPHI apparatus, using approximately 150 000 hadronic and leptonic events from 1989 and 1990, one determines the following Z0 parameters: the mass and total width MZ = 91.177 ± 0.022 GeV, ΓZ = 2.465 ± 0.020 GeV, the hadronic and leptonic partial widths Γh = 1.726 ± 0.019 GeV, Γl = 83.4 ± 0.8 MeV, the invisible width Γinv = 488 ± 17 MeV, the ratio of hadronic over leptonic partial widths RZ = 20.70 ± 0.29 and the Born level hadronic peak cross section σ0 = 41.84±0.45 nb. A flavour-independent measurement of the leptonic cross section gives very consistent results to those presented above (Γl = 83.7 ± 0.8rmMeV). From these results the number of light neutrino species is determined to be Nv = 2.94 ±0.10. The individual leptonic widths obtained are: Γe = 82.4±_1.2 MeV, Γu = 86.9±2.1 MeV and Γτ = 82.7 ± 2.4 MeV. Assuming universality, the squared vector and axial-vector couplings of the Z0 to charged leptons are: V ̄l 2 = 0.0003±0.0010 and A ̄l 2 = 0.2508±0.0027. These values correspond to the electroweak parameters: ρvarianteff = 1.003 ± 0.011 and sin2θW eff = 0.241 ± 0.009. Within the Minimal Standard Model (MSM), the results can be expressed in terms of a single parameter: sin2θW M ̄S = 0.2338 ± 0.0027. All these values are in good agreement with the predictions of the MSM. Fits yield 43